2010
DOI: 10.1176/appi.ajp.2009.09081130
|View full text |Cite
|
Sign up to set email alerts
|

Time to Attainment of Recovery From Borderline Personality Disorder and Stability of Recovery: A 10-year Prospective Follow-Up Study

Abstract: Objective The first purpose of this study was to determine time-to attainment of recovery from borderline personality disorder and the second was to determine the stability of this important outcome. Method 290 inpatients meeting both Revised Diagnostic Interview for Borderlines and DSM-III-R criteria for the disorder were assessed during their index admission using a series of semistructured interviews and self-report measures. The same instruments were readministered at five contiguous two-year time period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
154
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(176 citation statements)
references
References 20 publications
14
154
0
8
Order By: Relevance
“…[9][10][11][12] However, this is not unique to adolescents, as demonstrated in a recent 10-year prospective follow-up study that showed that up to 50% of adults with a BPD will eventually recover. 13 In contrast with the categorical diagnoses, it appears that a greater stability can be observed using a dimensional approach with selected symptom criteria, such as mood lability and anger dyscontrol, which emerge as significant predictors of BPD diagnosis in both adolescent and adult samples. 11,12,14,15 Thus conceptualizing BPD from a dimensional, rather than a categorical, approach could be particularly pertinent in adolescents, as a dimensional approach may better account for the developmental variability and heterogeneity observed during this age period.…”
Section: Limitationsmentioning
confidence: 94%
“…[9][10][11][12] However, this is not unique to adolescents, as demonstrated in a recent 10-year prospective follow-up study that showed that up to 50% of adults with a BPD will eventually recover. 13 In contrast with the categorical diagnoses, it appears that a greater stability can be observed using a dimensional approach with selected symptom criteria, such as mood lability and anger dyscontrol, which emerge as significant predictors of BPD diagnosis in both adolescent and adult samples. 11,12,14,15 Thus conceptualizing BPD from a dimensional, rather than a categorical, approach could be particularly pertinent in adolescents, as a dimensional approach may better account for the developmental variability and heterogeneity observed during this age period.…”
Section: Limitationsmentioning
confidence: 94%
“…8,9 One large, well-conducted 10-year prospective study found that 93% of those with borderline personality disorder had at least a 2-year period of remission, but only 50% also attained good psychosocial functioning. 10 In this article, we focus on the current diagnostic criteria for borderline personality disorder, as presented in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR), 11 and how these criteria can be used to differentiate it from other disorders that may share symptoms. A summary of the evidence used in this review is found in Box 1.…”
mentioning
confidence: 99%
“…For instance, Grilo et al (2004) reported that more than half of the patients in CLPS had remitted from their index diagnosis within two years, and Zanarini, Frankenburg, Reich, & Fitzmaurice (2010) found that 93% of the patients in the Mclean Study of Adult Development (MSAD) had remitted from borderline personality disorder in ten years. This research challenges longstanding assumptions that personaliy symptoms are highly stable, and provides hope for people with personality diagnoses But it also stands in marked contrast to research on basic traits, which show relative absolute stability at brief intervals despite agenormative changes across longer intervals (Roberts, Walton, & Viechtbauer, 2006).…”
Section: Constructsmentioning
confidence: 99%